Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00417-016-3394-y
|View full text |Cite
|
Sign up to set email alerts
|

Two-year, prospective, multicenter study of the use of dexamethasone intravitreal implant for treatment of macular edema secondary to retinal vein occlusion in the clinical setting in France

Abstract: PurposeTo evaluate patterns of use and long-term efficacy and safety of dexamethasone intravitreal implant (DEX implant) in the treatment of macular edema secondary to branch or central retinal vein occlusion (BRVO, CRVO) in French clinical practice.MethodsA 24-month, prospective, multicenter, longitudinal, observational study (LOUVRE) conducted at 48 randomly selected sites in metropolitan France enrolled consecutive adult patients with macular edema following retinal vein occlusion (RVO) who were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 18 publications
5
31
1
2
Order By: Relevance
“…Our study might have selected patients with comparatively worse treatment response with need for retreatment and therefore longer follow-up. This might also explain the lower rate of patients with a BCVA gain ≥15 letters after 24 months in our study (21.3%) compared with LOUVRE study (38.7%), while the rate of patients with BCVA gain ≥15 letters after 6 months was similar in both studies (32.9% vs 31.3% in LOUVRE) 10. Furthermore, data on anatomical outcomes in our study demonstrated that a proportion of the patients might have been undertreated, reflecting the scenario in the real-world setting.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Our study might have selected patients with comparatively worse treatment response with need for retreatment and therefore longer follow-up. This might also explain the lower rate of patients with a BCVA gain ≥15 letters after 24 months in our study (21.3%) compared with LOUVRE study (38.7%), while the rate of patients with BCVA gain ≥15 letters after 6 months was similar in both studies (32.9% vs 31.3% in LOUVRE) 10. Furthermore, data on anatomical outcomes in our study demonstrated that a proportion of the patients might have been undertreated, reflecting the scenario in the real-world setting.…”
Section: Discussionsupporting
confidence: 45%
“…The LOUVRE study reported a significant improvement of 4.8 letters in RVO eyes treated with DEX implant after 24 months 10. The better outcome reported in this trial compared with our results might be explained by its prospective design and a discontinuation rate of 26%, among others due to lack of treatment efficacy 10.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…As needed IDI regimens have been followed in treatment of various diseases, and efficacy of single injection has been found to be about 3 to 4 months (12-17). Korobelnik et al evaluated real-life outcomes of IDI in RVO patients in a multicenter prospective study conducted in France (12). Length of study follow-up was 24 months, and 279 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of visual loss in BRVO is ME [4][5][6][7]. There are some treatment options for macular edema such as intravitreal dexamethasone implants, laser treatment, and intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents [8,9]. These treatments have effects on resolution of ME.…”
Section: Introductionmentioning
confidence: 99%